Components of a healthy diet and different types of physical activity and risk of atherothrombotic ischemic stroke: A prospective cohort study - Johansson, Anna; Acosta, Stefan; Mutie, Pascal M.; Sonestedt, Emily; Engström, Gunnar; Drake, Isabel (Frontiers in Cardiovascular Medicine, 2022)
Both diet and physical activity (PA) are thought to influence the risk of ischemic stroke (IS). However, few studies have examined their effect on different subtypes of IS. The purpose this study was therefore to examine components of overall diet quality and different types of PA in relation to the risk of atherothrombotic IS (aIS). The study population included 23,797 participants (mean age 58 years; 63% women) from the Malmö Diet and Cancer Study cohort. Participants were followed from 1991-96 until end of 2019 (median follow-up 21.5 years). Incident aIS events were identified using national registries (total cases 1,937). Measures of PA (total, leisure-time, occupational, and domestic) were assessed using a baseline questionnaire and dietary intakes were estimated using a modified diet history method. Overall diet quality was assessed using a diet quality index. Intake of key food groups and beverages associated with overall diet quality were investigated separately. Hazard ratios (HR) and 95% confidence intervals (CI) were estimated using multivariable Cox regression models adjusting for confounders. A high diet quality with high intake of fruit and vegetables, fish and shellfish and low intake of SSB and red and processed meat compared to a low diet quality was associated with lower risk of aIS (HR:0.82, 95%CI 0.69-0.97; p=0.015). Leisure-time PA was associated with reduced risk of aIS (HR:0.95 per SD increase in MET-hours/week, 95%CI: 0.91-0.99; p=0.028) with null associations observed for total, occupational and domestic PA level. We observed no significant interaction between diet and PA on the risk of aIS. The standardized 20-year risk of aIS among subjects with low leisure-time PA and low diet quality was 8.1% compared to 6.1% among those with high leisure-time PA and high diet quality. Results suggests that several components of a healthy diet and being physically active may reduce the risk of aIS, however, the absolute risk reduction observed was modest. A high diet quality seemed to have a risk reducing effect regardless of level of PA suggesting that persons with a sedentary lifestyle may still gain some positive health benefits through a healthy diet.